The crisis of Marxism : a historical-intellectual problem - Palti, Elías José (Marx and Marxisms : new horizons, 2025)
In this book, Elías J. Palti analyzes the writings of key thinkers who have theorized the present situation of Marxism: Perry Anderson, Fredric Jameson, Ernesto Laclau, Slavoj Žižek, Judith Butler, Alain Badiou, and Jacques Derrida. His aim is to interrogate what appears to be the final crisis of Marxist political tradition from a historical-intellectual point of view, placing it within a broader framework, which is the present crisis of politics, at large. Yet, it also reveals why we cannot, even then, avoid confronting it, stubbornly trying to think of what seems to be unthinkable today, namely, the idea of an emancipatory horizon.Unlike traditional works of political philosophy, The Crisis of Marxism: A Historical-Intellectual Problem does not intend to provide political or philosophical answers to today's dislocation of politics. Instead, it aspires to clarify the nature of the questions that such a situation raises and demonstrates why the current crisis of Marxism contains some fundamental clues for it.